HMGA2 Promotes Brain Injury in Rats with Cerebral Infarction by Activating TLR4/NF-κB Signaling Pathway - Shaoyue Huang; Zhen Hong; Leguo Zhang; Jian Guo; Yanhua Li; Kuo Li (Hindawi Limited, 2022)
Cerebral infarction is a common disease with a higher disability and fatality rates. The incidence rates of cerebral infarction or cerebral ischemic stroke gradually increase with aging and cerebrovascular disease progression. This study is aimed at evaluating the effects of HMGA2 on cerebral infarction-induced brain tissue damage and its underlying mechanisms. Adult Sprague Dawley rats were pretreated with sh-HMGA2 before cerebral infarction operation. The effect of HMGA2 on the arrangement, distribution, and morphological structure of neurons and the cell apoptosis ratio in brain tissue were detected via hematoxylin and eosin staining, brain-water content, TTC staining, and TUNEL staining. The results from ELISA assay, qPCR, and western blot indicated that downregulation of HMGA2 mitigated inflammatory stress via regulating the expression of TLR4/NF-κB. In addition, results showed that suppressed HMGA2 attenuated the neurological dysfunction of brain injury rats and markedly reduced infarct volume. HMGA2 might be able to alleviate the damage associated with cerebral infarction-induced inflammatory response and cell apoptosis. Moreover, downregulation of HMGA2 had a protective effect on the brain damage derived from cerebral infarction by mediating the TLR4/NF-κB pathway. In conclusion, the current study demonstrated that downregulation of HMGB2 decreased the infarct size, inflammatory responses, and apoptosis in cerebral injury and further had neuroprotective effects against cerebral infarction-induced brain damage. Finally, these results indicated that the downregulation of the TLR4/NF-κB pathway after ischemia by HMGB2 inhibition is a potential mechanism of the neuroprotective effect of cerebral injury.